A single-nucleotide polymorphism C-724 /del in the proter region of the apolipoprotein M gene is associated with type 2 diabetes mellitus. Issue 1 (December 2016) - ZHANG, Pu-Hong; GAO, Jia-Lin; PU, Chun; FENG, Gang; WANG, Li-Zhuo; HUANG, Li-Zhu; ZHANG, Yao
Abstract Background Apolipoprotein M (apoM) was the carrier of the biologically active lipid mediator sphingosine-1-phospate in high density lipoprotein cholesterol (HDL-C) and played a critical role in formation and maturation of prebeta-HDL-C particles. The plasma apoM levels were decreased obviously in patients with type 2 diabetes mellitus (T2DM). A new single-nucleotide polymorphism (SNP) C-724del in apoM promoter was associated with a higher risk for coronary artery diseases (CAD) and myocardial infarction, could reduce promoter activities and apoM expression in vitro. The primary aim of the present case-controls study was to investigate the effect of apoM SNP C-724del on apoM expression in vivo and its association with T2DM susceptibility in an eastern Han Chinese cohort. Methods Two hundred and fifty-nine T2DM patients and seventy-six healthy controls were included in this study. Amplifying DNA of apoM proximal promoter region including SNP C-724del by Real-Time Polymerase Chain Reaction (RT-PCR) and amplicons sequencing. The plasma apoM concentrations were assayed by enzyme linked immunosorbentassay (ELISA). Results Four polymorphic sites, rs805297 (C-1065A), rs9404941 (T-855C), rs805296 (T-778C), C-724del were confirmed. rs805297 (C-1065A) and rs9404941 (T-855C) showed no statistical difference in allele frequencies and genotype distributions between T2DM patients and healthy controls just as previous studies. It's worth noting that the difference of rs805296 (T-778C) between these two groups was not found in this study. In SNP C-724del, the frequency of del allele and mutant genotypes (del/del, C/del) were higher in T2DM patients compared with healthy controls (p = 0.035;P = 0.040, respectively), while the plasma apoM levels of C-724del mutant allele carriers compared with the wide-type homozygotes carriers were not statistically different in T2DM patients (18.20 ± 8.53 ng/uL vs 20.44 ± 10.21 ng/uL, P = 0.245). Conclusion The polymorphism C-724del in the promoter region of the apoM gene could confer the risk of T2DM among eastern Han Chinese. Unfortunately, the lowing of plasma apoM levels of C-724del mutant allele carriers compared with the wide-type homozygotes carriers in T2DM patients was not statistically different in present study, so further researchs were needed by enlarging the sample.